Retracted article : nanoporous PtFe surface alloy architecture for enhanced methanol electro-oxidation - Qiu, Huajun (2013)
By selectively dealloying PtFeAl ternary alloy in 0.5 M NaOH solution, a novel nanoporous PtFe (npPtFe) alloy with nanorod-like morphology and inherent three-dimensional bicontinuous ligament-pore structure was successfully fabricated. X-Ray diffraction and electron microscope characterization demonstrated the crystal nature of the alloy ligament with ligament size down to 3 nm. NaOH concentration plays a key role in the formation of a uniform PtFe alloy structure. Dealloying solution with a low NaOH concentration (0.5 M) is suitable for the formation of a pure PtFe alloy structure, while Fe3 O4/np-PtFe nanocomposite is obtained when using a high NaOH concentration ($2 M). The np-PtFe alloy can be facilely converted into a nanoporous near-surface alloy structure with a Pt-rich surface and PtFe alloy core by a second dealloying process in dilute HNO3 solution. Electrochemical measurements show that the nanoporous near-surface alloy has greatly enhanced catalytic activity and durability towards methanol electro-oxidation compared with the state-of-the-art Pt/C catalyst. The peak current density of methanol electro-oxidation on the nanoporous surface alloy is about ﬁve times that on Pt/C. More importantly, continuous potential cycling from 0.6 to 0.9 V (vs. RHE) in 0.5 M H2 SO4 aqueous solution demonstrates that the np-PtFe surface alloy has a better structural stability than commercial Pt/C. With evident advantages of facile preparation and enhanced electrocatalytic activity and durability, the np-PtFe surface alloy holds great potential as an anode catalyst in direct methanol fuel cells.